ANALISIS PENGGUNAAN MEDIA FLASHCARD UNTUK ANAK SD KELAS 1 UNTUK MENINGKATKAN KETERAMPILAN PRAMEMBACA - Bella Pebrianti; Perdani, Puti Ayu; Fahrurohman, Oman (STKIP Subang, 2026)
Early reading skills are a fundamental component in developing students’ literacy abilities at the elementary school level, particularly in first grade. However, many students still experience difficulties in recognizing letters, combining letters into syllables, and understanding simple words. Therefore, appropriate learning media are needed to support the development of early reading skills. This study aims to analyze various research findings related to the use of flashcard media in improving early reading skills of elementary school students. The research employed a literature study (library research) method by reviewing relevant books, scientific articles, and research documents. Data sources were obtained from journal articles published between 2019 and 2025 through databases such as Google Scholar and Publish or Perish. Data collection was conducted through documentation techniques, while data analysis involved identifying, classifying, and analyzing the findings of previous studies. The results of the literature review indicate that the use of flashcard media has a positive impact on improving students’ early reading skills. Flashcards help students recognize letters, syllables, and simple words more easily through visual representations. In addition, the use of flashcards can enhance students’ motivation, interest, and active participation in learning, making the learning process more interactive and enjoyable.